HEALTH TECHNOLOGY ASSESSMENT: INTERNATIONAL EXPERIENCE - M.V. Avksent'eva; O.M. Omel'yanovskii (Union of pediatricians of Russia, 2011)
In modern conditions to provide the population with the high quality medical care it is necessary to assess the potentialities of a new technology in terms of actual practice. The article presents the historical background that determined the need for organizations to evaluate technologies in health care (HTA). Such an analysis allows us to establish specific guidelines and standards for the use of new technologies, identification of clear indications and priority groups of patients. The article presents the main functions of HTA agencies, as well as different approaches to the HTA in countries already having a similar experience. It is convincingly shown that the evaluation of new technologies before their widespread introduction into practice not only contributes to increasing the availability of the effective approaches to diagnosis and treatment of various diseases, but it is also regarded as an element of the state costs reduction to the health.Key words: health technology assessment, agency for the evaluation of medical technologies, evidence-based medicine, clinical and economic analysis, economic evaluation.